Research Progress on Solid-State Electrolytes in Solid-State Lithium Batteries: Classification, Ionic Conductive Mechanism, Interfacial Challenges - Shun Ai; Xianli Wu; Jintao Wang; Xu Li; Xiaofeng Hao; Yuezhong Meng (Nanomaterials)
Solid-state lithium batteries exhibit high-energy density and exceptional safety performance, thereby enabling an extended driving range for electric vehicles in the future. Solid-state electrolytes (SSEs) are the key materials in solid-state batteries that guarantee the safety performance of the battery. This review assesses the research progress on solid-state electrolytes, including polymers, inorganic compounds (oxides, sulfides, halides), and organic–inorganic composites, the challenges related to solid-state batteries in terms of their interfaces, and the status of industrialization research on solid-state electrolytes. For each kind of solid-state electrolytes, details on the preparation, properties, composition, ionic conductivity, ionic migration mechanism, and structure–activity relationship, are collected. For the challenges faced by solid-state batteries, the high interfacial resistance, the side reactions between solid-state electrolytes and electrodes, and interface instability, are mainly discussed. The current industrialization research status of various solid electrolytes is analyzed in regard to relevant enterprises from different countries. Finally, the potential development directions and prospects of high-energy density solid-state batteries are discussed. This review provides a comprehensive reference for SSE researchers and paves the way for innovative advancements in regard to solid-state lithium batteries.